Effect of Bainitisation Temperature on Phase Transformation Kinetics in Silicon-Alloyed Cast Steels - Saraczyn, R.; Deroszewska, M.; Marciniak, S.; Myszka, D. (Archives of Foundry Engineering, 2026)
This study investigates the effect of bainitisation temperature on the kinetics of phase transformation and the resulting microstructure in cast steels with two different silicon levels (0.87 wt.% and 2.06 wt.%). Cast steels were produced by induction melting and centrifugal casting. The remaining alloying elements were kept similar between alloys. A combined approach of JmatPRO simulations, high-resolution dilatometry, XRD, SEM, and Vickers hardness testing was used to characterise transformation temperatures, phase fractions, morphology and mechanical response. Results show that silicon exerts both thermodynamic and kinetic influences: thermodynamically, it tends to favour ferrite in equilibrium phase fields, while kinetically, it suppresses carbide precipitation during bainitic transformation, promoting carbon partitioning to austenite and thus increasing the fraction of retained austenite after austempering. Compared to the lower-Si alloy, the higher-Si alloy exhibits a bainitic transformation shifted to lower temperatures, higher hardness in fully transformed and quenched conditions, and larger retained-austenite fractions after isothermal bainitisation. Proper selection of bainitisation temperature in high-silicon cast steels enables favourable mechanical properties while retaining silicon-related benefits such as improved oxidation resistance and tempering stability.